The Principal's Role in Implementing TQM at Frateran Catholic High School, Surabaya: Exploring the Principal's Concrete Actions in Implementing TQM Principles at Frateran Catholic High School, Surabaya - Herman Emanuel Nggano; Imron Arifin; Bambang Budi Wiyono (al-Afkar, Journal For Islamic Studies, 2025)
The implementation of Total Quality Management (TQM) in education aims to improve school quality as a whole. This article explores the role of the principal of Frateran Catholic High School in Surabaya in implementing TQM principles. The study used descriptive qualitative methods through interviews, observations, and document analysis. The results indicate that the principal plays a significant role in leading the quality vision, developing teacher competencies, managing resources, and conducting ongoing evaluations. These findings indicate that the implementation of TQM has a positive impact on educational quality, although there are challenges that must be overcome. This article also provides suggestions for strengthening TQM implementation.